2015
DOI: 10.1080/10408398.2015.1069255
|View full text |Cite
|
Sign up to set email alerts
|

Advances on Bioactive Polysaccharides from Medicinal Plants

Abstract: In recent decades, the polysaccharides from the medicinal plants have attracted a lot of attention due to their significant bioactivities, such as anti-tumor activity, antioxidant activity, anticoagulant activity, antidiabetic activity, radioprotection effect, anti-viral activity, hypolipidemic and immunomodulatory activities, which make them suitable for medicinal applications. Previous studies have also shown that medicinal plant polysaccharides are non-toxic and show no side effects. Based on these encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
168
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(173 citation statements)
references
References 192 publications
3
168
0
2
Order By: Relevance
“…It was reported that polysaccharides could significantly inhibit pro-inflammatory mediators, such as TNF-α, IL-1β and IL-644. In this study, the levels of TNF-α and IL-6 in serum and homogenate of the model group were significantly higher than those in the normal control group.…”
Section: Resultsmentioning
confidence: 48%
“…It was reported that polysaccharides could significantly inhibit pro-inflammatory mediators, such as TNF-α, IL-1β and IL-644. In this study, the levels of TNF-α and IL-6 in serum and homogenate of the model group were significantly higher than those in the normal control group.…”
Section: Resultsmentioning
confidence: 48%
“…It is reported that APS can significantly improve experiment rat TNBS-induced colitis by regulating the expression of TNF-α, IL-1β and NFATc4. 47…”
Section: Astragalus Membranaceusmentioning
confidence: 99%
“…6)-D-Glcp and α-(1 ! 4)-D-Glcp in a molar ratio of 1: 47 The immunomodulatory activity of ASP has been extensively studied both in vitro and in vivo. It has been found that ASP increases the proliferation of total spleen cells, macrophages, and T cells by primary activation of non-specific immunity and secondary activation of helper T cells.…”
Section: Angelica Sinensismentioning
confidence: 99%
“…Polysaccharides are a class of natural macromolecular polymer with a molecular weight of tens of thousands even millions, which consist of more than 10 monosaccharides by glycosidic linkages . They are not only essential components of life, but also related to the regulation of biological signals .…”
Section: Biological Molecular Imprinting With Different Scalementioning
confidence: 99%